2021
DOI: 10.1017/s1478951520001455
|View full text |Cite
|
Sign up to set email alerts
|

Impact of palliative care on end-of-life care and place of death in children, adolescents, and young adults with life-limiting conditions: A systematic review

Abstract: Objective To determine the impact of palliative care (PC) on end-of-life (EoL) care and the place of death (PoD) in children, adolescents, and young adults with life-limiting conditions. Method Eight online databases (PubMed, Medline, EMBASE, Cochrane Library, CINAHL, Airiti, GARUDA Garba Rujukan Digital, and OpenGrey) from 2010 to February 5, 2020 were searched for studies investigating EoL care and the PoD for pediatric patients receiving and not receiving PC. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…A recent systematic review including 14 cohort studies and one case series found, that the receipt of PPC was associated with a decrease in intensive care use and high-intensity end-of-life care. Regarding hospital admissions, length of stay in hospital, resuscitation orders, and the proportion of hospital and home deaths results were less conclusive [ 16 ]. Evidence on healthcare resource utilisation and costs among children, who had accessed a PPC programme versus those, who had not, was summarised in a systematic review [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review including 14 cohort studies and one case series found, that the receipt of PPC was associated with a decrease in intensive care use and high-intensity end-of-life care. Regarding hospital admissions, length of stay in hospital, resuscitation orders, and the proportion of hospital and home deaths results were less conclusive [ 16 ]. Evidence on healthcare resource utilisation and costs among children, who had accessed a PPC programme versus those, who had not, was summarised in a systematic review [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Referral to palliative care reduced overall health care resource utilisation, maintained care continuity at the end of life [ 120 , 143 ], and facilitated access to integrative therapies during the end of life phase [ 115 ]. However, a systematic review reported conflicting evidence on palliative care collaboration benefits on hospital admissions at the end of life and resuscitation at the time of death [ 144 ].…”
Section: Outcomes Of Palliative Care Referral In Paediatric Oncologymentioning
confidence: 99%
“…Some of these strategies have well-documented benefits for patients/families and providers. For example, palliative care is associated with decreases in PICU use and high-intensity end-of-life care (121). That said, not all children with severe chronic illness who might benefit receive it (122, 123), and there is variation in its receipt across different chronic conditions (124, 125).…”
Section: Strategies Addressing Needs Of Children With Serious Chronic...mentioning
confidence: 99%